Is late bedtime an overlooked sleep behaviour? Investigating associations between sleep timing, sleep duration and eating behaviours in adolescence and adulthood. Issue 7 (10th May 2021) - Grummon, Anna H; Sokol, Rebeccah L; Lytle, Leslie A
Abstract: Objective: To examine whether bedtime is associated with usual sleep duration and eating behaviour among adolescents, emerging adults and young adults. Design: Cross-sectional multivariable regression models, stratified by developmental stage, to examine: (1) association between bedtime and sleep duration and (2) associations between bedtime and specific eating behaviours at each developmental period, controlling for sleep duration. All models adjusted for sociodemographic characteristics, depressive symptoms and screen time behaviours. Setting: National Longitudinal Study of Adolescent to Adult Health, waves I–IV, USA. Participants: A national probability sample surveyed in adolescence (aged 12–18 years, wave I: 1994–1995, n 13 048 and wave II: 1996, n 9438), emerging adulthood (aged 18–24 years, wave III: 2001–2002, n 9424) and young adulthood (aged 24–34 years, wave IV: 2008, n 10 410). Results: Later bedtime was associated with shorter sleep duration in all developmental stages, such that a 1-h delay in bedtime was associated with 14–33 fewer minutes of sleep per night ( P s < 0·001). Later bedtime was also associated with lower odds of consuming healthier foods (i.e. fruits, vegetables; range of adjusted OR (AOR), 0·82–0·93, P s < 0·05) and higher odds of consuming less healthy foods and beverages (i.e. soda, pizza, desserts and sweets; range of AOR, 1·07–1·09, P s < 0·05). Later bedtime was also associated with more frequent fast-food consumption and higher sugar-sweetened beverage consumption ( P s < 0·05). Conclusions: Later bedtime was associated with shorter sleep duration and less healthy eating behaviours. Bedtime may be a novel behaviour to address in interventions aiming to improve sleep duration and dietary intake.